The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.3171/jns.1997.87.2.0215
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid interleukin-1 receptor antagonist and tumor necrosis factor—α following subarachnoid hemorrhage

Abstract: Subarachnoid hemorrhage (SAH) causes an inflammatory reaction and may lead to ischemic brain damage. Experimental ischemia has been shown to be connected with the alarm-reaction cytokines interleukin-1 receptor antagonist (IL-1Ra) and tumor necrosis factor-alpha (TNF alpha). Increased levels of these cytokines, however, have not been detected thus far in patients following an SAH event. For this reason daily cerebrospinal fluid (CSF) samples were collected from 22 consecutively enrolled patients with SAH and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
118
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(125 citation statements)
references
References 40 publications
3
118
1
Order By: Relevance
“…In human studies, it was found that on admission, the IL-1ra level was higher (318 ± 302 pg /ml) in patients who were in poor clinical condition (Hunt and Hess Grades III -IV), and in patients with an unfavorable outcome or who experienced an episode of delayed ischemic deficit, there were marked increases in CSF IL-1ra levels between days 3 and 12 (>1000 pg /ml). On the contrary, patients with favorable outcome and good clinical condition had levels of IL-1ra only slightly higher than control patients (228,229).…”
Section: Il-1ramentioning
confidence: 91%
See 1 more Smart Citation
“…In human studies, it was found that on admission, the IL-1ra level was higher (318 ± 302 pg /ml) in patients who were in poor clinical condition (Hunt and Hess Grades III -IV), and in patients with an unfavorable outcome or who experienced an episode of delayed ischemic deficit, there were marked increases in CSF IL-1ra levels between days 3 and 12 (>1000 pg /ml). On the contrary, patients with favorable outcome and good clinical condition had levels of IL-1ra only slightly higher than control patients (228,229).…”
Section: Il-1ramentioning
confidence: 91%
“…Mathiesen et al (228) showed that on admission of patients suffering from SAH, CSF levels of TNF-a were similar to control patients (means 25 -52 pg /ml), and that in patients with an unfavorable outcome, i.e., Glasgow outcome scale 1 to 3, CSF levels of TNF-a were increased between days 4 and 10 to the range 200 -300 pg /ml. As for IL-1ra, the pattern of TNF-a levels fits with the time course of symptomatic VS or DID (delayed ischemic deficit) in humans.…”
Section: Tnf-+mentioning
confidence: 99%
“…11,12,29 There is broad consensus that SAH changes cerebrovascular function by inducing an inflammatory reaction within the vascular wall. 9,[30][31][32] Although several cytokines may be involved, [33][34][35][36] TNFα has garnered special attention because (1) cerebrospinal 33 and interstitial fluid 34 TNFα levels rise and peak between 4 and 10 days post-SAH (ie, a time-frame consistent with a role in DCI); (2) elevated TNFα levels associate with angiographic vasospasm, abnormal cerebral flow velocities, and poor clinical outcome [35][36][37] ; and (3) anti-TNFα therapy (infliximab) prevents basilar artery vasospasm in experimental SAH. 9 Our results demonstrate that TNFα augments olfactory artery myogenic tone in vitro; targeted disruption of TNFα signaling (TNFα and TNFα receptor 1 knockout models) confirmed this function in vivo after SAH.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that free radicals or cytokines are associated with the pathogenesis of cerebral vasospasm after SAH, 31,32 part of the mechanisms of vasospasm might be mediated by the activation of MAPK. Gerthoffer et al 7 and Hedges et al 8 have speculated that MAPK activation mediates cerebral vasospasm because MAPK activation induces the phosphorylation of caldesmon that, in turn, leads to vascular smooth muscle contraction.…”
Section: Mechanism Of Mapk Activation During Vasospasmmentioning
confidence: 99%